Analisis Penerapan Good Government Governance pada Pengelolaan Anggaran Pendapatan dan Belanja Desa (Studi Kasus pada Desa Pematang Johar, Kabupaten Deli Serdang) - Aldiansyah, Ferdy; Wirananda, Henny Andriyani (Jurnal EMT KITA, 2025)
This study aims to analyze the application of good government governance principles in the management of APBDes in Pematang Johar Village, Deli Serdang Regency starting from the planning, implementation, administration, as well as reporting and accountability stages. Researchers take three principles of good government governance which are used as variable indicators, including transparency, participation and accountability. The subjects in this study include the Chairman / Member of BPD, Village Head, Village Secretary and Treasurer, and community leaders of Pematang Johar Village. Research design is a guideline or procedure and technique in research planning that is useful as a guide for building strategies that produce research models. The research design conducted in this study is a qualitative method. Data collection techniques in this study used observation, interview and documentation methods. The data analysis method used in this study is qualitative descriptive analysis. The result of this study is that the management of APBDes in Pematang Johar Village, Deli Serdang Regency is broadly in accordance with the principles of good government governance, namely transparency, participation and accountability.